ANALYSIS OF THE EFFICIENCY OF MODERN IMPLEMENTATION METHODS OF DESIGN TEMPLATES IN OBJECT-ORIENTED PROGRAMMING - OSTAPCHUK, OLEKSANDR; SURYNOVYCH, ОLENA; LISHCHYNA, NATALIA; LISHCHYNA, VALERIY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Empirical evidence has been provided for the effectiveness of design patterns that can guide software development practices. The most effective design patterns for improving code quality, maintainability, and reusability were identified, which can help developers make informed decisions about pattern selection. The importance of balancing the benefits of design patterns with their potential drawbacks, such as increased code complexity, was emphasized. Research findings were described to inform pattern selection and the use of research recommendations to improve software development practice. This study included a survey of software developers to collect data on the use and effectiveness of design patterns in OOP. The study design was collected at one point in time. The survey questionnaire was developed based on a literature review of existing research on the use and effectiveness of design patterns in OOP. The study also highlighted the importance of balancing the benefits of design patterns with their potential drawbacks, such as increased code complexity. The study had several implications for the practice of software development. It highlighted the importance of using design patterns in OOP projects to improve code quality, maintainability, and reusability. The most effective design patterns to achieve these goals were also identified, such as the Factory method and observer patterns. In addition, it was emphasized the need to use design patterns wisely to avoid code complexity and performance issues. It was analyzed that the study can inform educational and training programs in software development, emphasizing the importance of design patterns and providing guidance on their effective use. A number of future scientific studies within the framework of this issue have been identified too.
Keywords: design patterns; object-oriented programming (OOP); patterns; software